"When nothing happens, nobody is afraid!" beliefs and perceptions around self‐care and health‐seeking behaviours: Voices of patients living with diabetic lower extremity amputation in primary care. Issue 6 (6th May 2021) - Zhu, Xiaoli; Lee, Mary; Chew, Evelyn AL; Goh, Ling Jia; Dong, Lijuan; Bartlam, Bernadette
Abstract: Self‐management and self‐care are the cornerstone of diabetes care and an essential part of successfully preventing or delaying diabetes complications. Yet, despite being armed with the required information and guidance for self‐management, self‐care and adherence to foot self‐care recommendations and compliance to medication among patients with diabetic foot ulcer and diabetic lower extremity amputations remain low and suboptimal. This study reveals in‐depth account of nine such patients' beliefs and perceptions around their illness, their self‐care, and their health‐seeking behaviours. Patients living with diabetic lower extremity amputation displayed profound lack of knowledge of self‐care of diabetes and foot and passive health‐related behaviours. The overarching sense that "when nothing happens, nobody is afraid, " points to a lack of motivation in taking charge of one's own health, whether this is with reference to treatment or care adherence, following recommended self‐care advice, or seeking timely treatment. The Health Beliefs Model provides the theoretical framework for probing into the factors for the participants' suboptimal self‐care and passive health‐seeking behaviours. Two themes emerged from data analysis: profound knowledge deficit and passive health‐related behaviours. The beliefs and perceptions around self‐care and health‐seeking behaviours for patients with lower extremity amputation are interpreted as the "ignorant self" with passive health‐seeking behaviours. Patients with diabetes and diabetic foot diseases may benefit from personalized education, motivational interviewing, and family support.